{Juvenile Cystic Adenomyoma vs Blind Uterine Horn: Challenges in the Diagnosis and Surgical Management.} - Protopapas, Athanasios; Kypriotis, Konstantinos; Chatzipapas, Ioannis; Kathopoulis, Nikolaos; Sotiropoulou, Maria; Michala, Lina (Journal of pediatric and adolescent gynecology, 2020)
BACKGROUND: Juvenile cystic adenomyomas (JCAs) are rare uterine lesions. Differential diagnosis might be difficult. We present the case of an adolescent who was diagnosed with JCA and was managed with laparoscopic excision. CASE: A 14-year-old patient with complaint of menarche with excruciating dysmenorrhea, was diagnosed using magnetic resonance imaging with a uterine anomaly consisting of a normal right hemiuterus, and a left cystic lesion with surrounding hypotense myometrium. She was managed with laparoscopic excision of the left side, and uterine reconstruction. Histology was suggestive of JCA, associated with diffuse adenomyosis. Dysmenorrhea improved considerably after surgery. SUMMARY AND CONCLUSION: Differential diagnosis between cystic uterine lesions relies on clinical, imaging, and perioperative clues that might assist in their formal classification. Doubt might still remain in some cases.